Strategic Management Accounting, Volume I Aligning Strategy, Operations and Finance - Joannidès de Lautour, Vassili (Springer International Publishing, 2018)
This book responds to key issues in strategic management control by studying the interplay between strategy, operations, finance and controls. Grounded in research but written with practitioners and students in mind, it addresses the most up-to-date management control issues in the public sector, forecasting, budgeting and controls in international organisations.